GATOR1-dependent recruitment of FLCN–FNIP to lysosomes coordinates Rag GTPase heterodimer nucleotide status in response to amino acids - Meng, Jin (J Cell Biol, 2018)
Folliculin (FLCN) is a tumor suppressor that coordinates cellular responses to changes in amino acid availability via regulation of the Rag guanosine triphosphatases. FLCN is recruited to lysosomes during amino acid starvation, where it interacts with RagA/B as a heterodimeric complex with FLCN-interacting proteins (FNIPs). The FLCN–FNIP heterodimer also has GTPase-activating protein (GAP) activity toward RagC/D. These properties raised two important questions. First, how is amino acid availability sensed to regulate lysosomal abundance of FLCN? Second, what is the relationship between FLCN lysosome localization, RagA/B interactions, and RagC/D GAP activity? In this study, we show that RagA/B nucleotide status determines the FLCN–FNIP1 recruitment to lysosomes. Starvation-induced FLCN–FNIP lysosome localization requires GAP activity toward Rags 1 (GATOR1), the GAP that converts RagA/B to the guanosine diphosphate (GDP)-bound state. This places FLCN–FNIP recruitment to lysosomes under the control of amino acid sensors that act upstream of GATOR1. By binding to RagA/B(GDP) and acting on RagC/D, FLCN–FNIP can coordinate nucleotide status between Rag heterodimer subunits in response to changes in amino acid availability.